Exploring the impact of a low-dose mindfulness intervention on perceived exertion, attention, and rowing - Bakken-Gay, R.; Junkersfeld, S. E.; Braun-Trocchio, R. (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: This study examined the effects of a four-week low-dose mindfulness intervention on ratings of perceived exertion, heart rate, attentional allocation, and performance outcomes, including power output, distance rowed, and strokes per minute, during a rowing task.